BATASAN USIA PERKAWINAN DALAM HUKUM KELUARGA ISLAM (Perbandingan Antar Negara Muslim: Turki, Pakistan, Maroko dan Indonesia) - Yulia Fatma (Institut Agama Islam Negeri Batusangkar, 2019)
Renewal of Islamic family law in the Islamic world is not a new thing, but it has been applied since the 19th century. The renewal was due to the rise of awareness of the community and scholars that the concepts of fiqh which had been used as references has been left behind from the times. The development of the situation and conditions of the community at that time was one of the causes of the reform of family law. This paper discussess about the family law that applies in several Muslim countries, namely the countries of Pakistan, Turkey, Morocco and Indonesia. Regulatory analysis carried out is by comparing family law that applied in each country regarding the age limit for marriage. The comparison analysis is vertical, horizontal, diagonal and the social conditions of these countries. Each country vertically has a different school handle, then horizontally these countries have provisions regarding the age limits of different marriages, both men and women due to the social conditions of the country itself. While diagonally related to the age limit of marriage, each country still adheres to the school they hold, although explicitly it is not determined how old the marriage is in the classical literature.